Naming and Fidelity of Truth: Rethinking Revolutionary Politics and Localizing, Delocalizing or Relocalizing the Void in Alain Badiou’S Philosophy; [Nombramiento y Fidelidad de la Verdad: Repensar la Política Revolucionaria y Localizar, Deslocalizar O Reubicar el Vacío en la Filosofía de Alain Badiou] - Letelier-Soto, A (Universidad Compultense Madrid, 2023)
This article explores the philosophy of Alain Badiou from the vantage point of the concepts of the localization, delocalization, and relocalization of the void as thematized through literary arts, religion, emancipatory politics, and the subject of psychoanalysis. In short, these moments around the void characterize the processes through which truth is processed and seen through their full realization by a philosophical engagement across the various conditions in which these truths occur. The localization of a void is the naming of an indiscernible element that is incommensurable to the rubric of constructible knowledge, sense and meaning which could saturate the space of truth. Thus, the naming that localizes the void acts as a subtraction of the invariant in the variance of situation such that across various points in space and time, we are still able to subtract the universal as the invariant not just as the fidelity to the localized truth but also as the resurrection of truth upon its relocalization at a different place and a different time. At its core, this article is concerned with truth, why truth is persistent, and why we have to struggle to articulate the truth that we are trying to be faithful to again and again with each instance that truth risks being covered-over and obscured. © 2023, Universidad Compultense Madrid. All rights reserved.